Situation Report: Czechoslovakia, 29 December 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Another Call from Prague for World Communist Meeting Three Prominent Dissidents Allowed/Compelled to Emigrate from Czechoslovakia Vietnamese Workers in Czechoslovakia Defense Spending Up in the 1983 Budget On CMEA Monetary Issues: Czechoslovak Attitude Compared Crime Statistics Dropped from Yearbook